(untitled) (Architecture Image Studies, 2020)
In this paper, I thematize the nature of the ephemeral image. This new kind of picture, which became popular across social media through the application Snapchat, offers a peculiar phenomenological experience for the user, which I mainly engage through the recent work of the German philosopher Lambert Wiesing. The main thesis of this work is that ephemeral images appear to their users with a greater degree of presence, enhancing their actuality and orality, and developing our memory capabilities.